Impact of Cash Flow Management on Shareholder Value of Listed Real Estate Companies in Vietnam - Phuong, To Lan; Thuy, Nguyen Thi Hong (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2021)
Many businesses have overlooked cash flow management and have resulted in failure or bankruptcy. According to surveys, up to 60% of losses are related to cash flow in the company. In this research, a group of secondary data from a selection of 56 listed real estate companies in Vietnam during the period of 2012-2019 is used to examine the relationship between cash flow management and shareholder value. The authors use a linear regression model and analysis to test for correlation between the variables. The results show that there is a non-significant relationship between the cash value-added and earning per share and there is a significant relationship between cash value-added and market value-added. Furthermore, the results also show a positive correlation between operating cash flow and market value-added. It is recommended that the scope of research should be expanded to other sectors and areas of the economy.